Intellectual Capital Efficiency and Sharia Banking Performance in Indonesia: Insights from 2015 to 2022 - Duyufur Rohman, Ghifary; Junio, Wilson (Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to analyze the influence of Intellectual Capital on the performance of Islamic commercial banks in Indonesia from 2015-2022. The research used a quantitative method with the Fixed Effect Model regression with secondary data obtained from the annual reports published by 9 Islamic commercial banks. The analysis results revealed that Intellectual Capital variables with VAHU, STVA, & and VACA and Financial Risk represented by NPF collectively exerted a significant impact on the performance of Islamic banks in Indonesia. However, partially, only VAHU indicators showed a significant positive effect on ROA. Conversely, VACA and NPF variables exhibited a significant negative influence on ROA, while STVA variables did not significantly affect ROA. The findings suggest a guide for Islamic banks to prioritize their investment in VAHU because of its significant contribution to profitability. In addition, Islamic banks need to increase investment in banking technology and R&D to improve the quality of service to customers. Also, implementing Current Accounts & Saving Accounts strategies to optimize Islamic bank assets and deliver optimal returns. Then, Islamic banks must address factors that affect the NPF rate, such as carefully selecting financing portfolios.